Samuel Kristeller (1820-1900) - K. N. Grigorieva (IRBIS LLC, 2020)
Samuel Kristeller (1820-1900) was one of the innovators in the XIX century German obstetrics and gynecology. In entire world, none of gynecologists and obstetricians could be unaware of knowing the name of such prominent human.